FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI DAN KEUNTUNGAN USAHA PETERNAKAN AYAM RAS PETELUR DI PROVINSI SULAWESI TENGAH - Afandi, Afandi (AgriSains, 2012)
The success of layer farmers business is economically dependent on the use of inputs necessary to produce the expected production. This research intent for: (1) know factors that regard egg production, (2) know factors that regard profit. The sampling method used census method. A total of sixty respondent’s farmer laying hens comprising thirty farmers from the city of Palu and thirty farmers of the Sigi’s Regency. Analysis’s tech data that is profit, analysis is bifilar linear regression. Result observation ling to point out layer farmer’s terminological small enterprise scale, medium, and big at Palu City and Sigi’s Regency that Production factors (input) one that ascendant positive to egg production layer farmers is total DOC and continent experience. Influential factor negative to profit are weft price and vitamin/medicine price, meanwhile dummy variable for scale intermediate positive ascendant.Key words: Laying farm, production, profit.